From rural to urban living – migration from Sami core areas to cities in Norway. Study design and sample characteristics - Melhus, Marita; Eliassen, Bent Martin; Broderstad, Ann Ragnhild (International Journal of Circumpolar Health, 2020)
The Indigenous Sami population have inhabited rural northern areas of Norway, Sweden, Finland and the Kola Peninsula in Russia for thousands of years. Today, many Sami live in cities. No large quantitative studies have investigated the health and life of urban Sami in Norway. As a basis for further research, this paper describes the background, methods, participation and sample characteristics of the survey From Rural to Urban Living , conducted in 2014. The unique sampling design is based on internal migration records. Those invited were everyone born 1950–1975 who had relocated from preselected rural Sami core areas to cities in Norway. Their children above the age of 18 were also invited. The paper is descriptive with some basic statistical tests. In total, 2058 (response rate 34%) first-generation and 1168 (response rate 19%) second-generation migrants responded. The response rate was lowest in the younger age groups and among men. One out of three reported Sami background. The education level was in general high. From Rural to Urban Living enables numerous research possibilities within health and social sciences, and may contribute to new insight into the health, culture and identity of the growing Sami population in urban areas of Norway.